ROLE AND FUNCTION OF FAMILY IN CARE OF PATIENTS WITH STROKE IN COMMUNITY - Agianto; Nuntaboot, Khanitta (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2018)
Background: The increasing of stroke prevalence is high year by year, and Indonesia is the number onefor cause of mortality. After three months, stroke survivors require long-term care. A stroke is a lifelongchange for both the stroke survivor and the family. Family caregiver is included in multidisciplinary thatshould provide the patients with stroke because of the unique demands on that population. There is lack ofstudy about stroke care in Indonesia.Objective: to explore the role and function of family in care of patients with stroke in community,Banjarmasin.Method: A critical ethnography design used in this study to explore and critically analyze role andfunction of family in care of patients with stroke in community. There were 15 key informants (familycaregivers) in this study using purposive sampling. Content analysis was used to answer the researchquestion.Result: Daily care activity, spiritual activity, rehabilitation and offering medicine, decision maker, andfinancial support are the role and function of family in care of patients with stroke in community setting.Conclusion: Family caregivers are playing an important role in caring for their relatives who havesuffered from strokes. They should work together with health workers to help the patient for enhancingthe quality of life of patient.